Quality Management in Islamic Schools (Madrasah): A Literature Review on Integrating Total Quality Management, PDCA, and Islamic Values into an IM-QM Model - Ahmad Munir; Andi Abdul Muis; Syahwal Syahwal; Ramli R.; Sunarti Sunarti (ARZUSIN, 2026)
Improving the quality of madrasah education requires the integration of modern management approaches with Islamic ethical values. This study aims to develop the Islamic Management Quality Model (IM-QM) by synthesizing Total Quality Management (TQM), the Plan–Do–Check–Act (PDCA) cycle, and core Islamic values, namely amanah, ihsan, itqan, and syura. Using a descriptive qualitative literature-review method, this study examined sources published between 2015 and 2025 from Scopus, SINTA, and Google Scholar, which were analyzed through content synthesis and triangulation. The findings indicate that TQM provides a strategic culture of continuous improvement and stakeholder orientation, PDCA offers an iterative operational mechanism for translating strategy into measurable practice, and Islamic values provide an ethical-philosophical foundation that legitimizes and humanizes quality improvement efforts. The integrated IM-QM model consists of three interdependent pillars: a philosophical pillar that embeds Islamic ethics into institutional purpose and decision-making, a managerial pillar that applies TQM principles for system-wide quality governance, and an operational pillar that uses PDCA cycles for planning, implementation, evaluation, and corrective action. The literature also identifies several implementation challenges, including partial adoption of TQM, limited translation of values into measurable indicators, resource and capacity constraints, and leadership gaps. These challenges underscore the need for participatory, value-driven leadership and measurable value-based quality indicators. This study concludes that IM-QM offers a holistic framework for strengthening academic and non-academic outcomes, stakeholder trust, institutional resilience, and religious identity in madrasah education. The study contributes to Islamic education management by proposing an integrated quality model and recommends further empirical validation through case studies, pilot implementation, and mixed-methods evaluation across diverse madrasah contexts.